Self-diffusion in polymer solutions using the bond-fluctuation MC-algorithm - Paul, Wolfgang; Heermann, Dieter W.; Kremer, Kurt (Journal of non-crystalline solids, 1991)
A lattice Monte Carlo study of the self-diffusion of polymer chains in an athermal solution of equal chains is presented. The examined chain lengths, N (= 20-200), and volume fractions, φ (= 0.025-0.5), cover the range from dilute solution to concentrated solution, respectively. The dynamics show a gradual crossover from Rouse to reptation-like behaviour. Analysing the data according to a scaling theory and taking into account the density dependence of the microscopic length and time-scales, an almost perfect scaling of the self-diffusion coefficient is achieved. The high statistical accuracy of the data (103-104 chains per parameter combination) was obtainable by using a transputer-based parallel computer.
Gesehen am 22.08.2017